Effects of different porous fillers on interfacial properties of poly (vinyl alcohol) hybrid films. Issue 27 (20th February 2021) - Wang, Sining; Huang, Zhen; Ru, Xiaofei; Wang, Jiting
Abstract: Poly(vinyl alcohol) (PVA)‐based hybrids have demonstrated broad liquid separation applications but separation performances are constrained by the compatibility between fillers and polymer, and thus it is essential to study the interfacial properties of these hybrids. In this work, PVA hybrids with four different porous fillers have been fabricated and characterized with Fourier transform infrared, X‐ray diffraction, Scanning electron microscope, swelling and contact angle tests. Swelling results show that PVA has a degree of swelling (DS) of 79% in water but the swelling is compressed after adding fillers and the DS for PVA hybrids has decreased by 19%, 17%, 15%, and 9% for 30 wt% loading of ZIF‐8, UiO‐66, Hβ and ZSM‐5, respectively. For methanol and its 10 wt% aqueous solution, similar swelling results are obtained due to mutual interactions among the filler, polymer and test liquids. Based on water and glycerol contact angle results, the surface energy of PVA is estimated to be 40.56 Nm −1 and it drops to 27.39 Nm −1 after adding less hydrophilic ZIF‐8 or rise to 48.56 Nm −1 after introducing more hydrophilic ZSM‐5. The high‐film hydrophilicity and then large surface energy have rendered methanol/water sorption selectivity of PVA hybrids decrease to some extent or vice versa. Abstract :